Nile Basin Development Challenge - An opportunity to achieve impact at scale - International Livestock Research Institute (International Livestock Research Institute, 2010)
Speaking at the Launch of the Nile Basin Development Challenge program (29 September 2010), ILRI Director General Carlos Seré explains why ILRI is partnering in a program focused on improved water management in Ethiopia and the Nile Basin. He emphasized how the type of integrative science envisaged in this Program is in line with directions envisaged for the new CGIAR.